Cochlear Implant Electrode Migration due to Cholesterol Granuloma: Cues from a Case - Di Laora, Andrea (J Int Adv Otol, 2019)
This paper aims to describe a rare case of cochlear implant (CI) failure due to electrode array migration and review the literature on the topic. A 72-year-old woman complained of retroauricolar pain two years after receiving a left CI, with deterioration of the auditory skills and an increased impedance of electrodes. Temporal bone computed tomographic scans revealed a soft density tissue involving the left mastoid and the middle ear. It also revealed a lateral displacement of the array into the middle ear. Surgery with CI re-implantation was performed. The specimen examination disclosed the presence of a cholesterol granuloma. According to the literature, array migration after CI due to cholesterol granuloma is very rare. When patient’s auditory performances decline and electrodes impedance increases, computed tomography (CT) scans should be performed to detect possible electrode issues, as in this case. Middle ear and mastoid cholesterol granuloma represent a possible, rare, cause of electrode array migration, even in absence of cochlear erosions.